Measurement of fecal T3 metabolite levels in sheep: Analytical and biological validation of the method - Pasciu, Valeria; Sotgiu, Francesca Daniela; Nieddu, Maria; Porcu, Cristian; Berlinguer, Fiammetta (Frontiers in Veterinary Science, 2022)
Biological sample collection from wild and farms animals is often associated with difficulties related to the handling and restraint procedures, and most of the time it could induce stress, altering the welfare and physiological homeostasis. The analysis of fecal T3 metabolites (FTMs) allows to test samples collected in a non-invasive manner, providing several information about the animal's physiological conditions and the effects related to environmental and nutritional variations. This procedure has found wide application in wild species, but less in domestic ones. The aim of this work was to validate the use of an immuno-enzymatic competitive ELISA kit, designed for T3 quantification in human blood serum samples, for the assessment of FTMs in the sheep. For the biological validation the variations of FTMs in relation to age, sex and the physiological status of the animal were determined. The same kit had been already validated for the mouflon fecal matrix in a previous work. After a verification of the precision (RSD % < 15%), mean recovery (75%) and parallelism (CV% < 10%), the kit was used to measure FTMs in cyclic, pregnant, and early lactating ewes as well as in rams and ewe lambs. The results showed that FTMs concentrations in pregnant ewes were significantly lower (p<0.05) than in cyclic and early lactation ones. Furthermore, there were no significant differences in FTMs levels between ewes and rams, while in lambs FTMs levels were higher than in adults (p<0.001). In conclusion the present study demonstrates that FTMs can be reliably and accurately determined in sheep feces, using an ELISA kit formulated for human serum T3 assay. The application of this method in the livestock sector could allow to improve our knowledge about the response of animals to different physiological and environmental conditions, and thus assess their welfare.